Adversities experienced by professionals in the Primary Healh Care: implications for the meanings of the work - Iluska Pinto da Costa; Cláudia Jeane Lopes Pimenta; Maria José Menezes de Brito
Abstract Objective: To understand the experiences of adversity in the Primary Health Care and their implications for the meanings of the participant professionals' work. Methods: Single case study, of qualitative nature, with 62 professionals active in the Family Health Strategy, whose data were collected by means of semi-structured interview and comics technique and analyzed by the thematic content analysis, with aid of Atlas ti, version 7 software. Results: There emerged the categories: Experiences of adversities in the Family Health Strategy and Implications of the adversities for the meaning of the professionals' work. In these categories were pointed aspects related to inadequate conditions of work, to wage question, to excessive demands and interpersonal conflicts that provided negative implications for the meanings of the team's work, for satisfaction and usefulness of the work. Conclusion: it was possible to apprehend the experiences of adversities in the work environment and its implications on the meanings of the work that can impair the professionals' actions. Implications for practice: the study may subsidize the reflection on the strategies that enable the reduction of the adversities in the work environment, contributing to benefiting the worker's health and care of quality for the population.